Isobaric vapor-liquid equilibrium data for the binary systems of dimethyl carbonate with xylene isomers at 93.13 kPa - Yadav, S.S. (Journal of Chemical and Engineering Data, 2017)
Isobaric binary vapor-liquid equilibrium (VLE) data for dimethyl carbonate with xylene isomers (p-xylene, m-xylene, o-xylene, and ethylbenzene) were measured at the local atmospheric pressure of 93.13 kPa by using a dynamic recirculation still. The experimental VLE data were tested and found to be thermodynamically consistent by Herington and Van Ness consistency test. The experimental VLE data were correlated using the Wilson, NRTL, and UNIQUAC activity coefficient models and binary interactions parameters were estimated using a suitable objective function. The absolute mean deviation between the experimental and the model predicted values of vapor phase composition and total pressure was well within acceptable limits. No azeotrope was observed in any of the binary pairs and appeared to be easy for separation using conventional distillation method.
Keywords: Atmospheric Pressure; binary mixture; Distillation; Xylene

Vapour–liquid equilibrium study of binary mixtures of aniline with isopropanol, n -butanol and ethylene glycol at the local atmospheric pressure - Mali, P.K.; Mali, N.A.; Yadav, S.S.; Joshi, S.S. (Indian Chemical Engineer, 2018)
The present work analyses the vapour–liquid equilibrium (VLE) behaviour of the binary systems of aniline with isopropanol, n-butanol and ethylene glycol. The isobaric VLE data have been generated at the local atmospheric pressure of 96.15 kPa for all the binary systems of aniline. A dynamic type vapour–liquid circulating VLE still was used for generating the data. Calibration curves were generated using mole fraction and refractive index data for all pairs for composition measurement. The VLE data, generated in T-x,y form for all pairs, were found thermodynamically consistent through the Herington area test and the mean absolute deviation test. Activity coefficient models, Wilson, NRTL and UNIQUAC, were fitted to the data to estimate binary interaction parameters using an objective function of minimising the deviation between the experimental and the calculated total pressure and vapour composition. The experimental data were compared with the model predictions with the estimated parameters and the model predictions were found appropriate. The binary system of aniline and ethylene glycol was found to exhibit azeotropic behaviour at 0.61 mole fraction aniline and 445.1 K.